Teoría austriaca del ciclo económico aplicada al caso espa\~nol: Del inicio del euro a la gran recesión y su recuperación; Austrian economic cycle theory applied to the Spanish case: from the begging of the euro to the great recession and its recovery - Miguel A. Alonso Neira; Antonio Sánchez-Bayón; Marcos Castro-Oliva (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– This is a research on Political Economy, Macroeconomics and Applied Economy, based on the Austrian Economics' approach over the economic cycles and applied to the Spanish case (2002-2014). Attention is focused on the endemic problem of economic cycles, such as successive and distorting periods of boom and recession that modern economies suffer, such as the Spanish economy. Thisis an inquire to find empirical evidence in favor of the Austrian Business Cycle Theory, for the specific Spanish case between 2002 and 2014, through the application of econometric methods. Consequently, after reviewing the scarce previous econometric literature on the Austrian cycle, this research has as its main objective to explain and illustrate the boom with the effective introduction of the euro in 2002, the recession during 2008-11 and the recovery in 2014, using the Austrian theory of the endogenous and non-neutral monetary cycle.
Keywords: B5; C58; E3; E4; E5; G2; 330; economic and business cycle; monetary policy; capital-based Macroeconomics; Austrian Economics; Heterodox approache